Matrine Protects Cardiomyocytes From Ischemia/Reperfusion Injury by Regulating HSP70 Expression Via Activation of the JAK2/STAT3 Pathway. Issue 6 (December 2018) - Guo, Suping; Gao, Chuanyu; Xiao, Wentao; Zhang, Jing; Qu, Yongsheng; Li, Jiang; Ye, Famin
Abstract : ABSTRACT: Studies have shown that matrine showed cardiovascular protective effects; however, its role and mechanism in myocardial ischemia/reperfusion (I/R) injury remain unknown. The Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3) pathway activation and elevated heat shock protein (HSP) 70 are closely related to the prevention of myocardial I/R injury. The cardioprotective effects of matrine were determined in hypoxia/reoxygenation (H/R)-treated primary rat cardiomyocytes and left anterior descending coronary artery ligation and reperfusion animal models. The molecular mechanisms of matrine in myocardial I/R injury were focused on JAK2/STAT3 pathway activation and HSP70 expression. We found that matrine significantly increased H/R-induced the suppression of cell viability, decreased lactate dehydrogenase release, creatine kinase activity, and cardiomyocytes apoptosis in vitro . Moreover, matrine notably reduced the serum levels of creatine kinase-myocardial band (CK-MB) and cardiac troponin I, lessened the infarcted area of the heart, and decreased the apoptotic index of cardiomyocytes induced by I/R in vivo . Matrine activated the JAK2/STAT3 signaling, upregulated HSP70 expression both in vitro and in vivo . The cardioprotective effects of matrine were abrogated by AG490, a JAK2 inhibitor, and HSP70 siRNA. In addition, AG490 reduced HSP70 expression increased by matrine. In conclusion, matrine attenuates myocardial I/R injury by upregulating HSP70 expression via the activation of the JAK2/STAT3 pathway.